On the stability of explicit finite difference schemes for a pseudoparabolic equation with nonlocal conditions - Jachimavičienė, Justina; Sapagovas, Mifodijus; Štikonas, Artūras; Štikonienė, Olga (Nonlinear Analysis: Modelling and Control, 2014)
A new explicit conditionally consistent finite difference scheme for one-dimensional third-order linear pseudoparabolic equation with nonlocal conditions is constructed. The stability of the finite difference scheme is investigated by analysing a nonlinear eigenvalue problem. The stability conditions are stated and stability regions are described. Some numerical experiments are presented in order to validate theoretical results.